2014
DOI: 10.1002/mnfr.201300931
|View full text |Cite
|
Sign up to set email alerts
|

Targeted metabolic profiling of pomegranate polyphenols and urolithins in plasma, urine and colon tissues from colorectal cancer patients

Abstract: Significant levels of EA derivatives and urolithins are found in human colon tissues from CRC patients after consumption of pomegranate. Further studies are warranted to elucidate their biological activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
199
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(204 citation statements)
references
References 38 publications
4
199
1
Order By: Relevance
“…In most situations, this is difficult to precisely determine, as in vivo metabolic studies are not available for most compounds. Although only a few such studies exist for pomegranate juice (Cerda et al 2003a,b, Mertens-Talcott et al 2006, Nielsen et al 2008, what is clear is that ingestion of 235 ml/day (about 8 ounces) of pomegranate juice results in detectable metabolites in the circulation (Mertens-Talcott et al 2006, Nunez-Sanchez et al 2014. We showed previously that antenatal ingestion of 235 ml/day of pomegranate juice is sufficient to reduce in vivo oxidative stress in the placentas of women who underwent labor .…”
Section: Discussionmentioning
confidence: 95%
“…In most situations, this is difficult to precisely determine, as in vivo metabolic studies are not available for most compounds. Although only a few such studies exist for pomegranate juice (Cerda et al 2003a,b, Mertens-Talcott et al 2006, Nielsen et al 2008, what is clear is that ingestion of 235 ml/day (about 8 ounces) of pomegranate juice results in detectable metabolites in the circulation (Mertens-Talcott et al 2006, Nunez-Sanchez et al 2014. We showed previously that antenatal ingestion of 235 ml/day of pomegranate juice is sufficient to reduce in vivo oxidative stress in the placentas of women who underwent labor .…”
Section: Discussionmentioning
confidence: 95%
“…P or HFD ? GT values were reported and expressed as foldbasal (n = 11) *P \ 0.05 versus CTRL, P \ 0.05 versus HFD Eur J Nutr Pomegranate and green tea extracts do not protect mice against HFD-induced obesity In human studies, the typical dose used for pomegranate extracts is about 1 g/day [25][26][27] and between 300 mg and 4 g/day for green tea extracts [28,29], which corresponds to 5-65 mg/kg body weight/day. Considering species differences, this corresponds roughly to 500 mg of extracts/kg body weight/day in mice [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…However, the main problem associated with the application of some plant-derived compounds is biological instability [13]. Previous studies showed that the incorporation of plant-derived compounds into nanoliposomes could overcome this limitation [14].…”
Section: Discussionmentioning
confidence: 99%
“…It has inhibitory effect on different kinds of cancer cells including prostate and colon cancer cells [11,12]. However, the in vivo instability of punicalagin has restricted its use in biomedical research [13]. Previous studies showed that encapsulation of plant-derived materials in nanocarriers such as nanoliposomes markedly reduced their in vivo instability and increased their effectiveness [14,15].…”
Section: Introductionmentioning
confidence: 99%